Internal audit assistance in the management of zakat, infak and shadaqah at LAZISMU Branch Malang City - Rahmad Hakim; Fitrian Aprilianto (Community Empowerment, 2024)
Zakat has a central role in improving the economic conditions of society, from those who previously lived in the shackles of poverty to become economically independent and prosperous. The aim of this community service is to improve the skills and understanding of Lazismu Malang City administrators as well as improve their abilities in internal auditing in the management of Zakat, Infaq, and Shadaqah so that zakat management can run effectively and efficiently. The methods used include surveys, internal audit workshops, training in making internal audit reports, and evaluation. The result of this effort is an increase in management's knowledge and understanding regarding internal audit by 60% and an increase in skills related to internal audit reporting by 75%. This increase in understanding shows that participants have a better understanding regarding internal audit in the management of zakat, infaq, and shadaqah.